Intermediate valence behaviour in the new Kondo lattice compound Yb3Ni5Al19 - Bauer, E. D. (2004)
The physical properties of single crystals of the Kondo lattice material Yb3Ni5Al19 have been investigated by means of magnetic susceptibility, specific heat, and electrical resistivity measurements. Single-crystal x-ray diffraction measurements indicate that Yb 3Ni5Al19 adopts the Gd3Ni 5Al19 orthorhombic crystal structure. This compound exhibits intermediate valence behaviour with a characteristic energy scale TK ∼ 500 K. Calculations of ∞(T) based on the Anderson impurity model within the non-crossing approximation including crystalline electric field effects are also presented.